Adsorption of Biologically Active Compounds from Aqueous Solutions on to Commercial Unmodified Activated Carbons. Part IV. Do the Properties of Amphoteric Carbon Surface Layers Influence the Adsorption of Paracetamol at Acidic pH Levels? - Artur P. Terzyk (Adsorption Science & Technology)
Three previously characterised, unmodified commercial activated carbons (D43/1, WD and AHD), differing in porosity and surface layer composition, were further examined using some additional methods of surface chemical description (electrochemical studies, acid–base site distribution, pH PZC and resistance measurements). Paracetamol adsorption isotherms (as well as kinetic curves) were measured on these carbons at acidic pH (1.5) and three temperatures, i.e. 300, 310 and 320 K. Measurements of the enthalpies of immersion in HCl and paracetamol solutions were also performed at 310 K, and diffusion coefficients and energies calculated. The results of measurements at acidic pH were compared with those obtained under neutral pH conditions. Some new correlations between the properties of the carbon surface and the constants characterising the process of paracetamol adsorption suggested recently were extended from data measured initially for six carbons. The mechanism of adsorption at both pH values was elaborated with the importance of surface carbonyls and basic groups being emphasised. The adsorption of the polymerisation product of paracetamol at acidic pH was determined using FT-IR and UV–vis spectroscopic measurements.